A retrospective analysis of factors affecting surgical site infection in orthopaedic patients. Issue 4 (April 2020) - Yang, Jun; Zhang, Xiangmin; Liang, Wangbo
Objective: To investigate the factors affecting surgical site infections (SSI) in patients undergoing orthopaedic surgery. Methods: The electronic medical records of patients undergoing orthopaedic surgery between September 2010 and July 2018 were retrospectively retrieved and reviewed. Logistic regression analyses were used to analyse the correlation between surgery-related variables and SSI. The odds ratio (OR) and 95% confidence interval (CI) were estimated for the risk factors. Results: Clinical data from 25 954 patients were reviewed and 804 (3.1%) were found to have become infected at the surgical site. Older age (≥60 years) was a risk factor (OR 2.218) and younger age (<18 years) was a protective factor (OR 0.258). Diabetes mellitus (OR 6.560) and hypertension (OR 3.991) were independent risk factors. Compared with type II incisions, type I incisions had a lower risk for SSI (OR 0.031), while type III incisions had a greater risk of SSI (OR 2.599). Compared with upper limbs and hands, the feet had a lower risk of infection, while surgery performed at the spine and joints did not increase the risk as compared with foot surgery. Conclusion: Older age, hypertension, diabetes mellitus and type III incisions were risk factors for SSI following orthopaedic surgery.